2018
DOI: 10.1530/jme-18-0009
|View full text |Cite
|
Sign up to set email alerts
|

C-peptide prevents SMAD3 binding to alpha promoters to inhibit collagen type IV synthesis

Abstract: Activation of transforming growth factor β1 (TGFB1)/SMAD3 signaling may lead to additional synthesis of collagen type IV (COL4), which is a major contributor to extracellular matrix (ECM) accumulation in diabetic nephropathy (DN). C-peptide can attenuate fibrosis to have unique beneficial effects in DN. However, whether and how C-peptide affects TGFB1/SMAD3-activated COL4 synthesis is unclear. In this study, pathological changes, expression of COL4 a1-a5 chains (), COL4 distribution and protein and TGFB1 and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Its signaling involves ERK1/2, PI3K-Akt, PKC, eNOS and NF-kB, well-known factors in TGF-β signaling [43,44], the key regulator of fibrosis, thereby suggesting C-peptide involvement in fibrogenic processes [45]. Indeed, recent studies show an association of C-peptide with fibrosis progression in different pathologies [46,47]. Some studies have reported the association of C-peptide with the transcription factor peroxisome proliferator-activated receptor-γ (PPARγ) [48], whose modulation balances adipogenesis and fibrogenesis [49], in line with the concept of metabolic dysregulation as an additional impacting cause of fibrosis, especially in IPF [45,49].…”
Section: Discussionmentioning
confidence: 99%
“…Its signaling involves ERK1/2, PI3K-Akt, PKC, eNOS and NF-kB, well-known factors in TGF-β signaling [43,44], the key regulator of fibrosis, thereby suggesting C-peptide involvement in fibrogenic processes [45]. Indeed, recent studies show an association of C-peptide with fibrosis progression in different pathologies [46,47]. Some studies have reported the association of C-peptide with the transcription factor peroxisome proliferator-activated receptor-γ (PPARγ) [48], whose modulation balances adipogenesis and fibrogenesis [49], in line with the concept of metabolic dysregulation as an additional impacting cause of fibrosis, especially in IPF [45,49].…”
Section: Discussionmentioning
confidence: 99%
“…Cpeptide can reduce albuminuria and glomerular ultrafiltration by reducing glomerular epithelial cell hypertrophy, mesangial expansion, tubular necrosis, tubulointerstitial inflammation, interstitial fibrosis, reabsorption of sodium in renal tubule, and glomerular hyperfiltration. 23,31,32 But, the relationship between excessive Cpeptide and DKD is yet to be elucidated experimentally. In addition, the incidence of DR is not high in the highest HOMA-IR group (G4).…”
Section: C-peptide and Diabeticmentioning
confidence: 99%
“…Diminished expression and activity of matrix-degrading enzymes and their natural inhibitors might also contribute to the accumulation of matrix in DKD 155,[158][159][160] .…”
Section: [H1] the Gbm In Glomerular Filtrationmentioning
confidence: 99%